Ethnicity, diversity and social relations in the city of Techirghiol (Dobrogea region) - Stănescu, Nina; Dan, Adrian-Nicolae; Tasențe, Tănase (Technium Social Sciences Journal, 2023)
The present study is based on research carried out in 2021 in the city of Techirghiol, a small town with approx. 8,300 inhabitants of Contanța county (Dobrogea region) in which we sought to explore ethnicity, diversity and social relations. After a description of the historical and socio-demographic context in which the populations and inter-ethnic relations were structured in Dobrogea, we presented the research methodology and analyzed the collected data. The research was quantitative, based on a questionnaire, in which 72 subjects were interviewed. The research conclusions show that in the city of Techirghiol there are harmonious inter-ethnic relations, without conflicts, but there is also a potential for improvement and superior mutual knowledge.